2018
DOI: 10.1111/nyas.13985
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis: developing new alternatives to reduce neuroinflammation and attenuate brain injury

Abstract: Sepsis occurs when a systemic infection induces an uncontrolled inflammatory response that results in generalized organ dysfunction. The exacerbated peripheral inflammation can induce, in turn, neuroinflammation which may result in severe impairment of the central nervous system (CNS). Indeed, the ensuing blood–brain barrier disruption associated with sepsis promotes glial activation and starts a storm of proinflammatory cytokines in the CNS that leads to brain dysfunction in sepsis survivors. Endotoxic shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 122 publications
0
51
0
2
Order By: Relevance
“…In addition, higher plasma levels of these inflammatory cytokines were observed in the ICU patients, which suggests that a cytokine storm presented in the severe patients [12]. This cytokine storm could induce various neurological symptoms and was previously reported to be able to disrupt the BBB and induce neuroinflammation in the sepsis [27,50,51]. In addition, the neutralizing antibodies (anti-S protein lgG), which are assumed to clear the virus and promote the recovery, can also cause severe secondary injury by altering inflammatory responses.…”
Section: Potential Mechanism Underlying the Neurological Manifestatiomentioning
confidence: 81%
“…In addition, higher plasma levels of these inflammatory cytokines were observed in the ICU patients, which suggests that a cytokine storm presented in the severe patients [12]. This cytokine storm could induce various neurological symptoms and was previously reported to be able to disrupt the BBB and induce neuroinflammation in the sepsis [27,50,51]. In addition, the neutralizing antibodies (anti-S protein lgG), which are assumed to clear the virus and promote the recovery, can also cause severe secondary injury by altering inflammatory responses.…”
Section: Potential Mechanism Underlying the Neurological Manifestatiomentioning
confidence: 81%
“…Clinical and experimental evidence link perinatal infection and inflammation to subsequent neurological and developmental sequelae (7). Sepsis can induce neuroinflammation resulting in activation of neurotoxic processes (8). There is increased risk of neurodevelopmental impairment in infants that experience sepsis and a meta-analysis demonstrated that coagulase-negative staphylococci sepsis in very low birth weight infants is associated with a higher incidence of cerebral palsy (9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other hypothalamic regions, as the SCN and PVN, are capable of receiving and modulating thermal signals (Lu et al, 2001;Wanner et al, 2013;Guzmán-Ruiz et al, 2015). Immune peripheral signals can reach the central nervous system by humoral or nervous pathways, which in turn can induce glial activation and the secretion of pro-or anti-inflammatory molecules (Meneses et al, 2019). Previous studies have shown neuronal activation in response to LPS (Hare et al, 1995;Marpegán et al, 2005;Paladino et al, 2010Paladino et al, , 2014, but this work provides the first indication of a circadian modulation in hypothalamic responses to high doses of this molecule.…”
Section: Discussionmentioning
confidence: 99%